Use of prescribed contraception in Northern Ireland 2010-2016 - Given, Joanne; Dolk, Helen; Gray, Ann Marie (International Journal of Population Data Science, 2018)
Background The risk of an unintended, potentially unwanted, pregnancy is related to whether or not a woman uses any method of contraception and which method she uses. We do not know if, or how, contraceptive use in Northern Ireland (NI) varies by age or deprivation. If, as in the rest of the United Kingdom, the younger and most disadvantaged are least likely to use contraception, or to use effective methods of contraception, they will be at increased risk of having an unintended pregnancy. Objectives To describe the use of prescribed contraceptives in NI and explore how this varies based on a woman’s age and the deprivation in the area in which she lives. As the prescriber plays a critical role in determining medication use we will also explore how the use of prescribed contraceptives varies based on characteristics of the woman’s general practice (GP) such as size of practice, urban/rural practice location and practice area deprivation. Method A population based cohort study, is being conducted through the Honest Broker Service, linking the GP Register to the Enhanced Prescribing database and 2017 NI Multiple Deprivation Measure for all females of reproductive age 2010-2016. Research based on administrative data is free from recall and social desirability bias, which may be present in surveys of contraceptive use. Administrative data cannot however identify use of over-the-counter contraceptives. Findings This project is still in progress and results will be available by the time of the conference. Based on the NI Statistics and Research Agency Mid-Year Population Estimates and the Business Services Organisation Pharmaceutical statistics there were an estimated 472,875 females between the ages of 12 and 49 living in NI 2010-2016 with 2,316,075 prescriptions for a contraceptive. Conclusions Administrative data should be regularly analysed to understand contraceptive use patterns, and address inequalities.